Permeabilidade ao vapor de pinturas exteriores. Influência na secagem de paredes - Carlos Rafael da Silva Oliveira (1997)
The study of the moisture migration in the in enveloping of buildings it is of great importance for its behaviour's characterization. Namely, in what concerns to durability, waterproofing, degradation appearance and in is thermal performance of the buildings elements.In the present study, the different ways of determination water-vapor permeability were studied. Based on simplified method of the drying walls, proposed by Mr. Vasco Freitas, was done the study of the paints permeability influence in the drying of the walls in relation to the inner and outer climate conditions.A data base with the water permeability values of several paints used in building construction was done. This base is fundamental to do the numerical simulation of moisture migration phenomenon in the vapor phase.Analyzing the experimental results of the water vapor permeability and the numerical results of the drying walls theoretical method, we get some important information about: the water vapor permeability variability in relation to the relative humidity; the water permeability in relation to the porous material structure; the influence of superficial resistance to the air water vapor in the calculation of the material permeability; the influence of the paints water vapor permeability in the drying of exteriors walls.Key words: Moisture, moisture migration, walls, water vapor permeability